SEJARAH NAGARI MAHAT SEBAGAI NAGARI SERIBU MENHIR DI KECAMATAN BUKIT BARISAN, KABUPATEN LIMA PULUH KOTA, SUMATERA BARAT - Oktavia Sesmita; Ridwan Melay; Tugiman Tugiman (Jurnal Online Mahasiswa (JOM) Bidang Keguruan dan Ilmu Pendidikan, 2018)
Abstract: Nagari is a settlement that has perfect governmental equipment, inhabited by several tribes with the top leader as the highest government leader. An area or village must have a name. Naming cannot be separated from the characteristics or matters relating to the background of the area. As with the name of the Mahat Nagari, dubbed as the Thousand Menhir Nagari.The purpose of this study is (1) How is the history of the formation of Nagari Mahat, Bukit Barisan District. (2) What is the distribution and number of historical relics in Mahat Nagari. (3) What is the role and function of menhirs in Mahat Nagari for the Mahat community in the past and present. In this study using qualitative research methods. Qualitative is a method that does not use numbers in data collection and in providing an interpretation of results. The results of this study are that civilization (ancient times) of the temple civilization and Islamic civilization. Mahat naming in this nagari there are several versions including the number of found or carved stones (menhir) with an amount of ± 1000 pieces. Menhirs and other historical relics found in the Mahat Nagari can be used as a historical tour with the concept of prehistoric travel.Keywords: History, Nagari, Menhir